Assessing the potential of Chlorella sp. phycoremediation liquid digestates from brewery wastes mixture integrated with bioproduct production - Wang, Sen; Zhao, Qiang; Yu, Haiyang; Du, Xinxin; Zhang, Ting; Sun, Tongxin; Song, Wenlu (Frontiers in Bioengineering and Biotechnology, 2023)
Digestates from different anaerobic digesters are promising substrates for microalgal culture, leading to effective wastewater treatment and the production of microalgal biomass. The aims of this study were to investigate the culture of Chlorella sp. in DigestateM from anaerobic fermentation of brewer`s grains and brewery wastewater (BWW) and to explore the potential use of the biomass produced under different experimental conditions. Cultivation in DigestateM initiated from 10% (v/v) loading, with 20% BWW, obtained maximum biomass production, reaching 1.36 g L-1 that was 0.27 g L-1 higher than 1.09 g L-1 of BG11. In terms of DigestateM remediation, the maximum removal of ammonia nitrogen (NH4+-N), chemical oxygen demand, total nitrogen, and total phosphorus reached 98.20%, 89.98%, 86.98%, and 71.86%, respectively. The maximum lipid, carbohydrate, and protein contents were 41.60%, 32.44%, and 27.72%, respectively. The growth of Chlorella sp. may be inhibited when the Y(Ⅱ)–Fv/Fm ratio is less than 0.4.